(3eLeY GdCeKGds - (3GdejOGfj , CHh GdaVd CMeO Hf eMeO Hf CMeO Hf EHQGgje GdejOGfj GdfjSGHhQj,J (B518 (3g` s ((3eMehO Hf eMeO Hf eMeO Hf eMehO CHh Ydi s)
(3ChdgG (B:s
(3Ef CMSf eG jhdL Hg UOQ GdcdGe hCLed eG jaUd Hg YbO GdfXGe MeO Gddg Pi GdLdGd hGdEcQGe aGdMeO ddg GdPi HOC Ndb GdEfSGf ef Wjf hCf cdGe fHjg Udi Gddg Ydjg hSde hgh CaUM GdYQH dSGfkG hCcedge OjfkG s
(3BNQgG (B:s
(3hbGd HYV GdSda KdGK jO HjVGA hgj GdEHJOGA hjO NVQGA hgj GdecGaCI hjO ShOGA hgj Gdef fLR GdcJGH s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B214 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B63s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1597s
Keywords: (3GdCOHs